Contribución a la relación taxonómica entre cuatro especies de peces de la familia Characidae mediante el Polimorfismo de ADN Amplificado al Azar (RAPD) (2004)
ABSTRACT: Information on taxonomic relationship among fish species is fundamental for an identification of wild populations. The family Characidae is a fish group widely distributed in Central and South America which must be identified, classified and preserved. Random Amplified Polymorphic DNA (RAPD) in this was used study to evaluate the taxonomic relationship in four tropical freshwater fish species located in Colombian territory, which belong to the family Characidae; subfamily Bryconinae: Brycon moorei and Brycon henni; and subfamily Serrasalminae: Colossoma macropomum and Piaractus brachypomus. Thirty four out of forty primers with sequences of ten nucleotides at random (RAPD) yielded 2.129 amplified DNA fragments, 428 of them were identified as specific markers that discriminated between genus and species. The fragment profiles showed that Brycon moorei got apart from the Brycon henni group, and inside this last group was possible to discriminate between samples from two different riverbasins; Magdalena and Cauca rivers. Piaractus brachypomus and Colossoma macropomum got apart from each other and distant from the subfamily Bryconinae. Furthermore, inside the Piaractus brachypomus group was possible to discriminate among individuals from the wild or the culture. The RAPD technique allowed an approach to the systematics in these species toward an appropriate identification.